KONASI MASYARAKAT TERHADAP PENGGUNAAN ARABIC TERMS DAN DESKRIPSI FINANCE SCHEME DALAM PEMASARAN PRODUK BANK SYARIAH (Analisa Pada Masyarakat Kota Yogyakarta) - Abdul Ghani (Universitas Alma Ata, 2012)
Abstract Sharia Banking in Indonesia have walked more or less two a decay and experience of the very growth of signifikan from year to year. But that progress not yet happened flattenedly. Because if comparated with the conventional bank growth is walked in advance mount the smaller that percentage a long way off. One of effort to increase enthusiasm of client of Indonesia Bank with the program of development of market segment and program the product development. During the time strive the product development of Sharia Banking more emphasizing at of service form and its transaction. Innovate to product of Sharia Banking even also is from time to time non-stoped to be developed and improved. Even to simply to differentiating characteristic among/between Sharia Banking with the conventional bank, crowded Sharia Banking embolden the islamication and arabication symbol and also its products. the symbol Eksklusivitas look coherent at name of product of Sharia Banking which always place forward the Arab terms (istilah-istilah arab), without reference to efficiency and the efektifity term use among plural society. Matter of that's becoming writer rationale to conduct this research This research analyse the arabic terms what is a lot of used in product of Sharia Banking, later then comparate with the use of finance scheme descripition explored with the terms have Indonesian. This research take the sample of urban community of Yogyakarta because assessed to represent the strategic region. Pursuant to hypothesizing, there no willingness difference of society konasi to use of arabic terms and use of finance scheme description in a few its product. type of Sample research used by cluster random sampling. This type of used by because wishing to know there is do not it him difference of society willingness of according to background of education and profession type/work. Sample research as much 150 respondent which is taken away from some of urban community Yogyakarta. In analyzing data gathered to be used aid of analyzer of data SPSS 17. Research analysis conducted through/passing test of two related sample test with the test analyse the sign test, k-independent sample test with the test analyse the Kruskal Wallis, and the two-independent sample test with the test analyse the Mann Whitney U test. Result of research show there are difference of society willingness to term use (arabic terms) and finance scheme description. Society more wishing of finance scheme description to be used in product marketing of sharia banking compared by Arabic terms. Keywords: arabic terms, finance scheme description, willingness, marketing, product.